Acquired and Participatory Competencies in Health Professions Education: Definition and Assessment in Global Health. (April 2017) - Eichbaum, Quentin
Abstract : Many health professions education programs in high-income countries (HICs) have adopted a competency-based approach to learning. Although global health programs have followed this trend, defining and assessing competencies has proven problematic, particularly in resource-constrained settings of low- and middle-income countries (LMICs) where HIC students and trainees perform elective work. In part, this is due to programs failing to take sufficient account of local learning, cultural, and health contexts. A major divide between HIC and LMIC settings is that the learning contexts of HICs are predominantly individualist, whereas those of LMICs are generally collectivist. Individualist cultures view learning as something that the individual acquires independent of context and can possess; collectivist cultures view learning as arising dynamically from specific contexts through group participation. To bridge the individualist–collectivist learning divide, the author proposes that competencies be classified as either acquired or participatory . Acquired competencies can be transferred across contexts and assessed using traditional psychometric approaches; participatory competencies are linked to contexts and require alternative assessment approaches. The author proposes assessing participatory competencies through the approach of self-directed assessment seeking, which includes multiple members of the health care team as assessors. The proposed classification of competencies as acquired or participatory may apply across health professions. The author suggests advancing participatory competencies through mental models of sharing. In global health education, the author recommends developing three new competency domains rooted in participatory learning, collectivism, and sharing: resourceful learning; transprofessionalism and transformative learning; and social justice and health equity.